Effect of breathing intervention in patients with COVID and healthcare workers - Manjari Rain; Goverdhan Dutt Puri; Aashish Bhalla; Pramod Avti; Balachundhar Subramaniam; Vipin Kaushal; Vinod Srivastava; Pranay Mahajan; Mini Singh; Navin Pandey; Pankaj Malhotra; Sonu Goel; et al. (Frontiers Media S.A., 2022)
BackgroundRegulated breathing facilitates ventilation and reduces breathlessness. However, the effect of Yogic breathing on patients with COVID remains unclear. We aimed to evaluate the efficacy of two breathing protocols, i.e., short breathing technique (SBT) and long duration breathing technique (LBDT).MethodsThree groups including COVID-positive patients, COVID-recovered patients, and healthcare workers (HCWs) were included in the study and segregated into Yoga and control groups. SBT was administered to COVID-positive patients. Both SBT and LBDT were administered to COVID-recovered patients and HCWs. A total of 18 biochemical parameters, a 6-min walk test (6MWT), and a 1-min sit-stand test (1MSST) were assessed on 0th, 7th, and 15th days, where biochemical parameters were the primary outcome. Pre-post estimation of neuropsychological parameters (nine questionnaires) and heart rate variability (HRV) were carried out. The paired t-test or Wilcoxon rank test was applied for pre-post comparison and the Student's t-test or Mann-Whitney U test was used for group comparison. Repeated measures test was applied for data recorded at three time points.ResultsA significant elevation in white blood cell (WBC) count was observed in COVID-positive intervention (p < 0.001) and control groups (p = 0.003), indicating no role of intervention on change in WBC number. WBC count (p = 0.002) and D-dimer (p = 0.002) significantly decreased in the COVID-recovered intervention group. D-dimer was also reduced in HCWs practicing Yogic breathing as compared to controls (p = 0.01). D-dimer was the primary outcome, which remained below 0.50 μg/ml (a cutoff value to define severity) in the COVID-positive yoga group (CYG) and decreased in the COVID-recovered yoga group (RYG) and the HCW yoga group (HYG) after intervention. A 6-min walk test (6MWT) showed an increase in distance covered among the COVID-positive patients (p = 0.01) and HCWs (p = 0.002) after intervention. The high-frequency power (p = 0.01) was found to be reduced in the COVID-positive intervention group. No significant change in neuropsychological parameters was observed.ConclusionYogic breathing lowered D-dimer, which is helpful in reducing thrombosis and venous thromboembolism in patients with COVID-19 besides lowering the chances of vaccine-induced thrombotic thrombocytopenia in vaccinated individuals. The breathing intervention improved exercise capacity in mild to moderate cases of COVID-19. Further studies can show if such breathing techniques can influence immunity-related genes, as reported recently in a study. We suggest that Yogic breathing may be considered an integrative approach for the management of patients with COVID.Trial registrationhttp://ctri.nic.in/Clinicaltrials/login.php, identifier: CTRI/2020/10/028195.